Development of IoT Kaizen System for smart lean raw material inventory management: a case study at an SME factory in Malaysia - Mohd Hazri Mohd Rusli,; Mohamad Khairi Hassan,; Suzilawati Muhamud-Kayat,; Elvianney Michael, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Effective Raw Material Inventory Management is crucial for overall company performance, demanding significant improvements. In the current technologically advanced landscape, the imperative adoption of the Internet of Things (IoT) is crucial for propelling inventory management forward and amplifying the visibility of raw materials. This case study is dedicated to developing an IoT Kaizen System, meticulously aligned with the Smart Lean Factory Inventory Control Framework, tailored to enhance Raw Material Inventory Management within an SME factory in Seremban, Negeri Sembilan. With a focal point on Loft Layer materials, the study encompasses Raw Material Ordering, Receiving, and Charging Out Log operations. Leveraging web-based tools such as Google Sheets, AppSheet, and Looker Studio, the system adeptly digitizes manual processes, tracking real-time data and integrating data visualization tools for informed decision-making. Implemented within a genuine industrial context, the project is intricately tailored to meet the unique preferences and requirements of the company, ensuring a customized solution that aligns with industry standards and reflects specific operational nuances. The resulting digital system introduces a structured, simplified, and efficient approach to Raw Material Inventory Management, injecting enhanced operational control and adaptability into the company’s workflow. Through the system implementation, warehouse space was reduced by 15%, order processing was done fully digitally that achieve zero case of ordering error and achieved zero case of material stock out. This system can adjust to what’s needed in modern manufacturing. It proves that using innovation and technology can make a business better by making things run more smoothly and helping with decision-making.